Feeding ecology of the scops owl, Otus scops (Aves: Strigiformes), in the island of Pianosa (Tuscan Archipelago, Central Italy) outside the breeding period. Issue 3 (2nd July 2016) - Mori, E.; Mazzetto, F.; Menchetti, M.; Bodino, N.; Grasso, E.; Sposimo, P.
ABSTRACT: All of the published studies but one about the diet of the Eurasian scops owl Otus scops, a nocturnal raptor of conservation concern, were carried out during the breeding period, just before or immediately after the chicks fledged. The species is a trans-Saharian migrant with few resident populations in Europe. Orthoptera make up the staple of its diet in summer. In this study, we investigated the diet of scops owls on the island of Pianosa after the breeding period through the analysis of pellets. A total of 327 fragments belonging to at least 14 taxa were identified from 56 pellets collected after the breeding period, between late August and March. By frequency, invertebrates constituted 80.00% of the diet, with Coleoptera being the most represented order (62.35% of the total diet) and Orthoptera poorly represented (8.24%). Vertebrates included two bird species, three small mammals and the Moorish gecko. Although the meal-to-pellet interval for scops owls is unknown, we suggest that the bank vole, which is not recorded on any Italian island, and possibly the wild mice, may have been preyed upon in nearby areas, before a migratory movement towards a warm area (e.g. Pianosa) occurred.